(untitled) (Research, Society and Development, 2021)
Its objective was to analyze how Physical Education teachers understand Law 10.639/03 and approach Afro-Brazilian culture in their classes. For this, a qualitative, descriptive and cross-sectional procedure was adopted. Ten Physical Education teachers from two public schools participated in the research. Data were collected through semi-structured interviews and treated using the content analysis technique. The results indicated that most teachers are unaware of Law 10.639/03 and that they had no contact with it during their professional training. Of the most developed content during their classes, games stood out, followed by sports and dance, being the least mentioned ethnic-racial issue. Regarding the approach to the contents related to the Afro-Brazilian culture, only one teacher affirmed to work on such contents throughout the academic year and in the subject program. Of the difficulties mentioned, the prejudice of the school community in relation to the theme stood out, even though teachers consider it important to deal with these contents, especially due to the diversity, miscegenation and racial prejudice present in Brazilian society. Therefore, it was concluded that there are still gaps both in relation to teacher training (initial and continuing) and in terms of knowledge, legitimacy and applicability of Law 10.639/03 and the contents of Afro-Brazilian culture in the school environment.